2006
DOI: 10.1177/070674370605101002
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Opioid Use and its Key Characteristics: A Select Overview and Evidence from a Canadian Multisite Cohort of Illicit Opioid Users (OPICAN)

Abstract: Clinical Implications • Illicit opioid use to a large extent manifests via the illicit use of prescription opioids and typically includes polysubstance use. • Physical and (or) mental health comorbidities are highly prevalent in illicit opioid user populations. • Morbidity and (or) mortality risks are often associated with social marginalization. Limitations • Little is known about the patterns and consequences of illicit opioid use in general populations. • Owing to the marginalized and illegal status of illi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 104 publications
(132 reference statements)
1
33
0
2
Order By: Relevance
“…At least in Vancouver, this is consistent with the literature; the proportion of women in MMT in British Columbia is 34.8%, 25 36.3% in the Supervised Injection Facility Cohort, 53 and 48.8% in a cohort of illicit opioid users not in treatment. 54 In Montreal, the available data shows differences in the female proportion by study. For example, the OPICAN study had 19.8% females, 54 similar to the 16.7% of the St. Luc Cohort study with IDUs.…”
Section: Discussionmentioning
confidence: 99%
“…At least in Vancouver, this is consistent with the literature; the proportion of women in MMT in British Columbia is 34.8%, 25 36.3% in the Supervised Injection Facility Cohort, 53 and 48.8% in a cohort of illicit opioid users not in treatment. 54 In Montreal, the available data shows differences in the female proportion by study. For example, the OPICAN study had 19.8% females, 54 similar to the 16.7% of the St. Luc Cohort study with IDUs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of PO injection have risen worldwide, including in the United States (Davis and Johnson, 2008;Young et al, 2010;Surrat et al, 2011;Lankenau et al, 2012;Black et al, 2013;MateuGelabert et al, 2015), Europe (Partanen et al, 2009;Keijzer and Imbert., 2011;Roux et al, 2011), South Asia (Larance et al, 2011) and Australia (Degenhardt et al, 2006). In Canada, over the past decade, PO injection has gained in popularity among drug users across the country (UHRI, 2013; Leclerc et al, 2013;Firestone and Fischer, 2008;Roy et al, 2011;Roy et al, 2013;Bruneau et al, 2012;Fischer et al, 2006;PHAC, 2014). Data from I-Track, a multisite surveillance system that monitors HIV and hepatitis C virus (HCV) infection rates and associated risk behaviors among persons who inject drugs (PWID) in Canada, revealed that hydromorphone, morphine and oxycodone, either in tablet or capsule form, were injected more often than heroin.…”
Section: Introductionmentioning
confidence: 99%
“…Injection drug users (IDUs) suffer an increased burden of infectious disease, co-morbid health conditions and elevated mortality rates in comparison to the general population (Fischer, Firestone-Cruz, & Rehm, 2006;Spittal, Hogg, Li, Craib, Recsky, Johnston et al, 2007). Further, IDU is linked to a multitude of vulnerabilities and social disadvantages (e.g., poverty, homelessness, mental illness), involvement in high-risk illegal income generating activities (e.g., sex work, drug dealing), and public disorder behaviours (e.g., public injecting), that also contribute to compromised health and well-being (Galea & Vlahov, 2002;Fischer et al, 2006;DeBeck, Shannon, Wood, Li, Montaner, & Kerr, 2007; DeBeck, Small, Wood, Li, Montaner, & Kerr, 2009;Miller, Pearce, Moniruzzaman, Thomas, Christian, Schecter et al, 2011). Consequently, IDUs are a highly marginalised and stigmatised population with multiple and complex needs, yet are hard to reach with mainstream health care services (Ahern, Stuber, & Galea, 2006;Simmonds & Coomber, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…IDU is prevalent among homeless and street-involved individuals (Kerr, Marshall, Miller, Shannon, Zhang, Montaner et al, 2009;Miller et al, 2011), and high rates of co-occurring mental disorders among IDU are well documented (Fischer et al, 2006;Aitken, Wain, Lubman, Hides, & Hellard, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation